ANALISIS PEMBIYAAN SYARIAH TERHADAP PENINGKATAN PENJUALAN ELEKTRONIK DI ERAFONE BANDAR LAMPUNG - Odi Herdian; Noorikha Pandayahesti Saputeri; Warsiyah (Program Studi Ekonomi Syariah, 2026)
The electronics industry in Indonesia has been growing rapidly along with the increasing use of digital devices by the public. However, high prices remain a major obstacle for consumers who wish to purchase products in cash. Islamic financing has emerged as an alternative financial system based on the principles of fairness, transparency, and interest-free transactions, making it an attractive option for Muslim consumers. This study aims to examine the influence of Islamic financing on the increase in electronic product sales at Erafone Bandar Lampung and its impact on consumers’ purchasing power. The research uses a descriptive qualitative method, with data collected through interviews, observations, and document studies at the Erafone Panjang Bandar Lampung branch. Data analysis was carried out systematically through the stages of data reduction, presentation, and conclusion drawing. The results show that Islamic financing contributes positively to the increase in electronic product sales, especially among consumers who prioritize transactions in accordance with Islamic principles. The main factors influencing customer interest include contract clarity (akad), price transparency, and ease of the application process. Challenges faced include a lack of consumer understanding, complicated administrative procedures, and competition with conventional financing. Marketing strategies using the marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) have proven effective in strengthening Erafone’s position in attracting Islamic financing consumers. This study recommends improving consumer education, employee training, and expanding cooperation with Islamic financial institutions to maximize the potential of Islamic financing in increasing electronic product sales